Repeatability and sensitivity of passive mechanical stiffness measurements in the triceps surae muscle‐tendon complex. (12th October 2021) - Walker, Josh; Bissas, Athanassios; Wainwright, Barney; Hanley, Brian; Cronin, Neil J.
Abstract : Measurements of muscle‐tendon unit passive mechanical properties are often used to illustrate acute and chronic responses to a training stimulus. The purpose of this study was to quantify the inter‐session repeatability of triceps surae passive stiffness measurements in athletic and non‐athletic populations, with the view to discussing its usefulness both as a muscle‐tendon profiling tool and a control measure for studies with multiple data collection sessions. The study also aimed to observe the effects of quiet standing on passive stiffness parameters. Twenty‐nine men (10 cyclists, nine triathletes, 10 controls) visited the laboratory on three separate occasions, where passive stiffness tests were carried out using an isokinetic dynamometer and B‐mode ultrasound. Participants were fully rested on two of the sessions and subjected to 20 min of quiet standing in the other. The passive stiffness assessment generally showed only moderate inter‐session repeatability but was still able to detect inter‐group differences, with triathletes showing higher passive stiffness than cyclists ( p < 0.05). Furthermore, quiet standing impacted passive stiffness by causing a reduction in ankle joint range of motion, although mechanical resistance to stretch in the muscle‐tendon unit at a given joint angle was relatively unaffected. These findings show that passive stiffness assessment is appropriate for detecting inter‐group differences in the triceps surae and even the effects of a low‐intensity task such as quiet standing, despite showing some inter‐session variation. However, the inter‐session variation suggests that passive stiffness testing might not be suitable as a control measure when testing participants on multiple sessions.